2007
DOI: 10.1038/nmeth1018
|View full text |Cite
|
Sign up to set email alerts
|

Imaging receptor microdomains on leukocyte subsets in live mice

Abstract: We present a simple method to identify the recruitment of leukocyte subsets and determine concurrent surface-receptor clustering in live mice. We show that CD45+ F4/80- Gr-1+ neutrophils are robustly recruited in surgery-activated cremasteric venules, whereas adherent CD45+ B220+ B lymphocytes were dominant in bone marrow venules. Most adherent Gr-1+ leukocytes are not firmly stationary but actively migrate on TNF-alpha-activated cremasteric venular endothelium and exhibit marked polarization of surface PSGL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 16 publications
1
81
0
2
Order By: Relevance
“…Multiphoton microscopy is extremely useful for studying distinct populations of leukocytes outside the vasculature, where dynamic events are sufficiently slow so that they can be observed using time-lapse systems, but it cannot be used to track leukocytes in the vasculature due to slow imaging speed. Recently, Frenette and colleagues (43) reported that high-speed, high-resolution multichannel fluorescence intravital videomicroscopy could be used to track different leukocyte subsets in response to a cytokine. We used similar spinning disk multichannel fluorescence intravital videomicroscopy (for the first time to our knowledge) to examine the very early dynamic events in blood vessels during CS.…”
Section: Discussionmentioning
confidence: 99%
“…Multiphoton microscopy is extremely useful for studying distinct populations of leukocytes outside the vasculature, where dynamic events are sufficiently slow so that they can be observed using time-lapse systems, but it cannot be used to track leukocytes in the vasculature due to slow imaging speed. Recently, Frenette and colleagues (43) reported that high-speed, high-resolution multichannel fluorescence intravital videomicroscopy could be used to track different leukocyte subsets in response to a cytokine. We used similar spinning disk multichannel fluorescence intravital videomicroscopy (for the first time to our knowledge) to examine the very early dynamic events in blood vessels during CS.…”
Section: Discussionmentioning
confidence: 99%
“…Specific leukocyte subset adhesion. To examine adhesion of specific leukocyte subsets, confocal intravital microscopy was used (35,36). To enable identification of specific leukocyte subsets, mice received the following Abs (eBioscience, San Diego, CA): anti-Gr-1-PE (0.8 mg) to label neutrophils, and anti-CD4-FITC (2 mg) and anti-CD8-allophycocyanin (2 mg) to label CD4 + and CD8 + cells, respectively, administered i.v.…”
Section: Histologymentioning
confidence: 99%
“…29,30 To discriminate accurately between leukocyte subsets, we injected intravenously very low amounts of fluorescently conjugated leukocyte-specific antibodies at the time of imaging, a procedure that does not alter the dynamic behavior of intravascular leukocytes. 31 T lymphocytes were thus distinguished by CD4 labeling, and neutrophils by Gr-1 labeling ( Figure 1A; see also Supplemental Figure S2 at http://ajp.amjpathol.org). Under noninflammatory conditions, about one-third of passing neutrophils were found rolling on dermal microvessels (see Supplemental Figure S2 at http://ajp.amjpathol.org).…”
Section: In Vivo Imaging Of Inflammatory T-lymphocyte Recruitment In mentioning
confidence: 99%